Peran Abusive Supervision Dalam Mempengaruhi Emotional Exhastion dan Work Performance Pada PT. Transporindo Agung Sejahtera Surabaya (PT. TAS) - Rizka Nanda Pratama Yudha; Dewi Nuraini (CV. Aksara Global Akademia, 2024)
The purpose of this research is to determine how unfair supervision impacts employee loneliness with emotional exhaustion as a mediating variable and organizational justice. This research involved employees of PT. TRANSPORINDO AGUNG SEJAHTERA SURABAYA (PT. TAS), a company that is growing rapidly. Questionnaires, interviews, and observations were used to collect data, and the sample was one hundred workers. The data collected was analyzed through mediation analysis, and documentation, interviews, literature studies, and questionnaires were used. The research results show that unfair supervision has a positive and significant impact on worker peace of mind. Abusive supervision disrupts organizational fairness, whereas abusive supervision increases emotional exhaustion. Mediation analysis was used to analyze the data collected, and documentation, interviews, literature studies, and questionnaires were used. The results show that unfair supervision significantly increases employee peace of mind, whereas arbitrary supervision disrupts organizational justice. Emotional exhaustion causes employees to become silent.